STRATEGI PEMASARAN PENDIDIKAN MELALUI MEDIA SOSIAL DI MIN 1 PARIGI - EFENDI, MUHAMMAD RIZAL; IQBAL, MUH.; RIFAD, MOH. (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2024)
The purpose of this research is to address the research focus on marketing strategies in education using social media. The approach used in this study is a qualitative approach with a descriptive research design. The researcher employed many methods for data collection, including observation, interviews, documentation, and analysis through data reduction, data presentation, and data verification. In order to ensure the validity and credibility of the obtained data, a validation check is conducted. The field research results indicate that the implementation of marketing strategies at MIN 1 Parigi has met the criteria of the components in the marketing mix, including planning, organizing, strategy, and social media selection.  MIN 1 Parigi has already utilized social media as a marketing tool for the school. The social media platforms utilized by MIN 1 Parigi for marketing purposes include Facebook and WhatsApp. The challenges or influences resulting from educational marketing through social media are evidenced by the annual increase in the number of students, ranging from 5 to 10%. Then, the school became known to the wider community, both within Parigi city and from outside Palu city. As a result of education marketing through social media, parents/guardians can register their children at MIN 1 Parigi, and prospective new students can view the school's profile through social media. Additionally, with education marketing through social media, the school is able to compete with other schools, especially in the field of education marketing. ABSTRAKTujuan penelitian ini adalah untuk menangani fokus penelitian pada strategi pemasaran dalam pendidikan menggunakan media sosial. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan desain penelitian deskriptif. Peneliti menggunakan banyak metode untuk pengumpulan data, termasuk pengamatan, wawancara, dokumentasi, dan analisis melalui pengurangan data, presentasi data, dan verifikasi data. Untuk memastikan validitas dan kredibilitas data yang diperoleh, pemeriksaan validasi dilakukan. Hasil penelitian lapangan menunjukkan bahwa implementasi strategi pemasaran di MIN 1 Parigi telah memenuhi kriteria komponen dalam campuran pemasaran, termasuk perencanaan, organisasi, strategi, dan pemilihan media sosial. MIN 1 Parigi telah menggunakan media sosial sebagai alat pemasaran untuk sekolah. Platform media sosial yang digunakan oleh MIN 1 Parigi untuk tujuan pemasaran termasuk Facebook dan WhatsApp. Tantangan atau pengaruh yang timbul dari pemasaran pendidikan melalui media sosial dibuktikan oleh peningkatan tahunan dalam jumlah siswa, berkisar dari 5 hingga 10%. Kemudian, sekolah itu menjadi dikenal masyarakat yang lebih luas, baik di dalam kota Parigi maupun di luar kota. Sebagai hasil dari pemasaran pendidikan melalui media sosial, orang tua / wali dapat mendaftarkan anak-anak mereka di MIN 1 Parigi, dan calon siswa baru dapat melihat profil sekolah melalui social media. Selain itu, dengan pemasaran pendidikan melalui media sosial, sekolah mampu bersaing dengan sekolah-sekolah lain, terutama di bidang pemasaran edukasi.